314 'Stop, don't chop the cord! Optimal cord management in premature babies'. (17th August 2022) - Stockley, Elizabeth; Aguirre, Diana; Busby, Samantha; Causer, Adele; Sunsoay, Gurpreet; Surana, Pinki
Abstract : Aims: Optimal Cord Management (OCM), (delayed cord clamping >1 minute), is recommended for all newborns, especially for those born preterm. Retrospective data collected over a three-month period (January-March 2021) from our tertiary maternity centre showed that OCM had been attempted in 17 of the 26(65%) babies born <32 weeks gestation with only 13(50%) achieving OCM. We aimed to implement a quality improvement (QI) project to improve the rates of OCM in babies born <32 weeks gestation. Methods: A multidisciplinary (MDT) QI project was launched from April to December 2021. Several interventions were implemented through Plan-Do-Study-Act (PDSA) cycles. PDSA 1 : A working group consisting of midwifery and neonatal educators was set up. Diagnostic tools were used to identify areas of improvement. PDSA 2 : A questionnaire was distributed to all perinatal staff to gain insight of current knowledge and local barriers to OCM; and in-situ MDT simulation occurred. PDSA 3 : Small group teaching on OCM was arranged with regular reinforcement of good practice during neonatal handovers. PDSA 4: A training video and posters were distributed via e-mail, WhatsApp messenger and on a closed social media page to all perinatal staff. PDSA 5 : A standard operating procedure was ratified and uploaded on the local trust intranet. PDSA 6: OCM was included in regular weekly obstetric simulation programme. PDSA 7 : Post-implementation questionnaire was distributed to all perinatal staff and in-situ MDT simulation occurred. Results: Questionnaire responses identified neonatal hypothermia, need for resuscitation and poor communication amongst the perinatal team as key concerns to OCM. These concerns along with risks and ergonomics through diagnostic QI tools led to changes in practice. This included optimal positioning of the resuscitaire, the introduction of a thermal suit with the cord intact, supporting the obstetric team with the initial respiratory support, and improving communication between the MDT and parents prior to the delivery. Outcome: Of the 98 babies born <32 weeks gestation between April-December 2021, 4 had contra-indications for OCM (abruption). Following PDSA 1 and 2 the rates of OCM improved, likely secondary to the questionnaire emphasising the need for OCM. However, improvements were not sustained and there was a significant decrease in OCM after PDSA 3. This could be due to the mode of teaching used, as improvements were only consistent after OCM was included in regular simulations, through PDSA 6 (see figure 1 ). Between September-December 2021, OCM was attempted in 23 of the 27(85%) babies, with 21(78%) receiving OCM, demonstrating a significant improvement when compared to baseline data. The reasons for OCM not being attempted or achieved were mainly due to babies' clinical condition or the maternity decision-making. Conclusion: Through our PDSA cycles, significant improvements were demonstrated in OCM in preterm babies. Increased awareness and education of the MDT stakeholders is effective in improving OCM but needs to be implemented on a continual basis to gain sustained benefits. With established MDT education around this QI, we hope to sustain and continue to improve our current level of performance.